Expression of periferal core molecular clock genes in oral mucosa depends on the chronotype in patients with maxillofacial cellulitis - Kateryna Lokes; Vitaliy Lychman; Olga Izmailova; Oksana Shlykova; David Avetikov; Igor Kaidashev (Elsevier, 2023)
Introduction: Accurate determination of the patient's chronotype is one of the problems of personalized medicine. Recent studies have shown that determining of the expression of timing genes is a valuable method that can help gain molecular insight into a patient's intrinsic circadian timing. Odontogenic cellulitis is very common pathology. Since acute inflammatory diseases are an urgent pathology, the time of surgical intervention can correspond depend on the time of the patient's hospitalization. Materials and methods: The level of mRNA expression of peripheral circadian clock genes clock and bmal1, per1, cry1 in buccal epithelial cells in patients with odontogenic purulent inflammatory diseases of maxillofacial area in the morning and evening was investigated. Results: During analyzing the results of the mRNA expression study of the genes of the negative regulatory link of the peripheral molecular clock, per1 and cry1, in patients with Cellulitis of the maxillofacial area, a significant decrease (P = 0.0003) in the mRNA expression level of the cry1 gene by 2.61 times in the evening compared to its morning mRNA expression values. Conclusion: The obtained data indicate that in patients with odontogenic purulent inflammatory diseases of the maxillofacial area with an evening chronotype, a violation of the expression profile of the per1 gene in the cells of the buccal epithelium is noted, which is manifested by an increase in its evening expression in comparison with patients with a morning chronotype.